Pemerolehan Bahasa Anak 2 Tahun 6 Bulan : Rerata Panjang Ujaran - Lizri, Kurniati Ramadhani; N, Nikmah; F, Fatmawati (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine language acquisition in children aged 2 years and 6 months using the Mean Length of Utterance (MLU) indicator. The approach used is qualitative with a descriptive design through a case study method on a child with the initials AAZ who lives in the Rokan Hulu region. The research data consists of child speech collected through the listening and speaking method with recording and note-taking techniques in natural communication situations. The results of data transcription and grouping show that there are 84 utterances with a total of 221 morphemes. The calculation of the RPU produces a value of 2.63. Based on the classification of RPU stages, this value places AAZ in group III which is characterized by the development of sentence structure. The research findings indicate that AAZ's language acquisition develops faster than children of the same age. However, AAZ's phonological and morphological abilities have not fully developed optimally, as indicated by the omission of initial phonemes and inaccuracies in the pronunciation of certain phonemes. This research is expected to contribute to our understanding of early childhood language development and serve as a reference for psycholinguistic studies, particularly regarding first language acquisition.